Developing an Innovative Pandemic Treaty to Advance Global Health Security. Issue 3 (2021) - Gostin, Lawrence O.; Meier, Benjamin Mason; Stocking, Barbara
Abstract: Recognizing marked limitations of global health law in the COVID-19 pandemic, a rising number of states are supporting the development of a new pandemic treaty. This prospective treaty has the potential to clarify state obligations for pandemic preparedness and response and strengthen World Health Organization authorities to promote global health security. Examining the essential scope and content of a pandemic treaty, this column analyzes the policymaking processes and substantive authorities necessary to meet this historic moment.